2012
DOI: 10.7762/cnr.2012.1.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workplace-Visiting Nutrition Education on Anthropometric and Clinical Measures in Male Workers

Abstract: The purpose of this study was to investigate effect of nutrition education at worksite program in male workers. The subjects were 75 male workers who had received nutrition education by a clinical dietitian for 4 months. The anthropometric data, blood pressure and biochemical blood indices were measured before and after nutrition education. Dietary habits and lifestyle were investigated by self-administered questionnaires. Nutrients intake was determined by 24-hour dietary recall method. The results showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
1
21
0
2
Order By: Relevance
“…Previous research has evaluated workplace health promotion programs in terms of a focus on nutrition 3 - 5) , PA 6 - 9) , stress management 10 - 12) , and tobacco cessation 13 , 14) . Of particular interest, the workplace has the potential of reaching a significant proportion of employed adults 15) , and this group of adults spends a large proportion of their time at work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has evaluated workplace health promotion programs in terms of a focus on nutrition 3 - 5) , PA 6 - 9) , stress management 10 - 12) , and tobacco cessation 13 , 14) . Of particular interest, the workplace has the potential of reaching a significant proportion of employed adults 15) , and this group of adults spends a large proportion of their time at work.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has evaluated workplace health promotion programs in terms of a focus on nutrition [3][4][5] ,PA [6][7][8][9] , stress management [10][11][12] , and tobacco cessation 13,14) .O fp a rticular interest, the workplace has the potential of reaching a significant proportion of employed adults 15) , and this group of adults spends a large proportion of their time at work. Therefore, the workplace is an ideal target area to promote health behaviors of worker populations and to conduct repeated multilevel interventions to influence health behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, nutrition education provided at work is especially beneficial for the employees that cannot visit the medical centers, because of the work schedule. From the welfare view, it can also boost the work ambition of employee (13). The importance of nutrition education programs depends on the level of their effectiveness (14).…”
Section: Introductionmentioning
confidence: 99%
“…The successful experiences of organizations in modifying bad eating habits of the employees have shown that changing their menu, as well as, introducing foodstuff, such as fresh fruit and vegetables, processed bread, fish , dairy products, different vegetable salad and boiled food, can significantly decrease the levels of blood lipid and weight gain (34). Results of Kim et al's research on 75 workers showed that providing continuous and regular nutrition programs for the employees were very effective in maintaining their optimal health and reducing risk factors, such as elevated levels of triglyceride and lipid (35). As a result, enhancing the level of employees' nutritional awareness by including appropriate nutrition programs presented by nutritionists, distributing and installing leaflets and posters related to healthy and balanced diet in the workplace can prevent the prevalence of obesity among the workforce.…”
Section: Discussionmentioning
confidence: 99%